Declarative Agent Languages and Technologies IX 9th International Workshop, DALT 2011, Taipei, Taiwan, May 3, 2011, Revised Selected and Invited Papers - Sakama, Chiaki; Sardina, Sebastian; Vasconcelos, Wamberto; Winikoff, Michael; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the thoroughly refereed post-proceedings of the 9th International Workshop on Declarative Agent Languages and Technologies, DALT 2011, held in Taipei, Taiwan, in May 2011. The volume contains 6 revised selected presented at DALT 2011, 7 best papers from the DALT series over the years, explaining how the research developed and how it influenced and impacted the community, the state-of-the-art and subsequent work, and two invited papers from the DALT Spring School, which took place in April 2011.
Keywords: Computer science; Computer Communication Networks; Software engineering; Logic design; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Models and Principles; Computer Communication Networks; Software Engineering; Programming Languages, Compilers, Interpreters; Logics and Meanings of Programs